Enhancing Music Art Learning Outcomes Through the Model of Cooperative Learning of Talking Stick Type at Students Grade IX 2 SMP Negeri 5 Muara Bungo - Asmiwirda, Asmiwirda (The Future of Education Journal, 2023)
Arts and culture education, as part of the subjects that must be mastered by students is one of the aspects that must be considered to form quality human beings, especially in appreciating musical works of art. This research is Classroom Action Research. Data collection techniques were obtained using observation, formative tests and documentation. The data analysis technique used is qualitative and quantitative analysis. The results showed that the application of the Talking Stick learning model was well received. This can be seen from the students who were initially shy about expressing their opinions in front of the class, eventually being more courageous and confident in expressing their opinions in front of the class. This learning model motivates students to be active and continue to learn in the learning process. Besides that, students become more active, enthusiastic and interested in participating in the process of learning the art of music where students are able to work together with members of their groups and are able to increase individual and group responsibility. The results of learning the art of music students as follows. The average student score was 55.79% in pre-cycle conditions, 70.91 in cycle I, 81.97 in cycle II. The criterion for the success of this research is if a minimum of 75% of students achieve a KKM score of 70. The successive classical learning completeness data is 9.09% in pre-cycle conditions, 45.45% in cycle I, and in cycle II 90.91% . The data above are interpreted with a qualitative range showing very poor categories in pre-cycle conditions, lacking in cycle I conditions, very good in cycle II. Based on the data above, it can be shown that the application of the Talking stick type Cooperative learning model can improve the learning outcomes of music arts in class IX 2 students of SMP N 5 Muara Bungo in the 2018-2019 Academic Year